IMPLEMENTASI BUDAYA KERJA PEGAWAI NEGERI SIPIL DALAM PELAYANAN PUBLIK DI KANTOR CAMAT SUNGAI APIT KABUPATEN SIAK - Sari, Elvika Permata; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is based on the existence of problems such as the habits of civil servants who are often late for scheduled working hours and enter and leave the office without valid explanation, there are still frequent violations of regulations and the Core values of Morality are still not fully implemented by every civil servant at the Sungai Apit Subdistrict Office Siak district. This research aims to describe the implementation of civil servant work culture and the reasons why civil servant work culture is not yet optimal in public services at the Sungai Apit Subdistrict Office, Siak Regency, using work culture theory according to Taliziduhu Ndraha. Then, this research also uses a qualitative descriptive research approach, where the type of data used is primary data from key informants and secondary data that is relevant to the research context. Data collection techniques used include interview techniques and documentation. Next, the data analysis technique uses qualitative descriptive analysis techniques to answer the research questions asked. The results of this research show that the work culture of civil servants at the Sungai Apit sub-district office is influenced by the habits of civil servants who often violate working hours and do not follow applicable regulations and there are several factors that influence the work culture of civil servants in public services at the Sungai Apit sub-district office. This resulted in public services at the Sungai Apit Subdistrict Office being hampered so that they did not reach the optimal level as expected. Keywords: Implementation, Work Culture, Civil Servants, Public Services